Chronique et autobiographie dans les Mémoires du duc de Saint-Simon - Marc Hersant (Carnets)
Saint Simon’s Memoirs, tightened between the model of the chronicle and that of the autobiography, articulate throughout two different and confuse projects: on the side of the chronicle, the subject remains uncertain, the memorialist hesitating between a diary of the life of court, a general picture of France in his period, and an occasional extension in Europe; on the side of the narrative of his own life, the will to limit itself to a political autobiography is overwhelmed by the feelings of the writer. The writing of the reality seems incapable of being reduced in a clearly defined genre.